Background and design of the Physical Frailty and Symptom Monitoring and Management Behaviors in Heart Failure (PRISM-HF) study: A mixed methods study - Quin E. Denfeld; Shirin O. Hiatt; Susan J. Rosenkranz; S.Albert Camacho; Christopher V. Chien; Nathan F. Dieckmann; Tyler B. Ramos; Christopher S. Lee; Barbara Riegel; Lissi Hansen (International Journal of Nursing Studies Advances)
Background: Many adults with heart failure (HF) are physically frail and have worse outcomes. While the biological profile of physical frailty in HF has been examined, the behavioral profile remains unstudied. Physical frailty may impact self-care behaviors, particularly symptom monitoring and management (SMM), which in turn results in adverse outcomes. This paper describes the background and design of a study that addresses this knowledge gap, entitled “Physical Frailty and Symptom Monitoring and Management Behaviors in Heart Failure” (PRISM-HF). Study design and methods: PRISM-HF is a sequential mixed methods study where in Phase 1, we collect quantitative data from a sex-balanced sample of 120 adults with HF, and in Phase 2, we collect qualitative data from ∼32–40 adults from this sample, aiming to: (1) quantify associations among physical frailty, SMM behaviors, and outcomes; (2) describe the experience of SMM behaviors for physically frail and non-physically frail adults with HF; and (3) identify the SMM behavioral needs of physically frail and non-physically frail adults with HF. At baseline, we measure symptoms, SMM behaviors, and physical frailty and collect clinical events at 6-months. We will use generalized linear modeling and survival analysis in Aim 1, directed content analysis in Aim 2, and triangulation analyses using an informational matrix in Aim 3. Conclusions: This innovative study will investigate the behavioral underpinnings of physical frailty in HF, incorporate the patient's perspective of SMM behaviors in the context of physical frailty, and identify possible explanations for the effect of physical frailty on outcomes.